The Impact of Freedom to Learn in Kampus Merdeka at Karyadarma University Kupang, East Nusa Tenggara - Drikben Eka Putra Nggadas; Hery Wadu; Greogorius Nenabu; Aloysius Liliweri; I Nengah Dasi Astawa (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2022)
The purpose of this research is to describe the impact of freedom to learnon Kampus Merdekaat Karyadarma University, Kupang, East Nusa Tenggara, Indonesia. This research was carried out with the Survey Method. The subject of this research is the entire academic community of Karyadarma University Kupang which consists of Lecturers, Education Personnel and Students. The data collection techniques and instruments used in this research are survey techniques using online questionnaires developed by the Spada Dikti Team. The data obtained were analyzed using descriptive analysis techniquesand regresianalysis. The result showed that the impact of freedom to learnon Kampus Merdekaat Karyadarma University Kupang is reflected through the implementation of the learning process, improvement of student soft and hard skills, improvement of student skills and capacity building of lecturers and education staff. The correlation of knowledge about freedom to learnin Kampus Merdekawith an increase in student soft and hard skills and an increase in student skills is in the weak category, while the correlation of knowledge about freedom to learnin Kampus Merdekawith an increase in lecturer capacity is in the high category